The rise of Candida auris: from unique traits to co-infection potential - Nadine B. Egger; Katharina Kainz; Adina Schulze; Maria A. Bauer; Frank Madeo; Didac Carmona-Gutierrez (Microbial Cell, 2022)
Candida auris is a multidrug resistant (MDR) fungal pathogen with a crude mortality rate of 30-60%. First identified in 2009, C. auris has been rapidly rising to become a global risk in clinical settings and was declared an urgent health threat by the Centers for Disease Control and Prevention (CDC). A concerted global action is thus needed to successfully tackle the challenges created by this emerging fungal pathogen. In this brief article, we underline the importance of unique virulence traits, including its easy transformation, its persistence outside the host and its resilience against multiple cellular stresses, as well as of environmental factors that have mainly contributed to the rise of this superbug.